Development of Low-Cost Precision Scanner System for Scanning Probe Microscopy Application - Kang, Qin Yee (2015)
Atomic Force Microscope (AFM), also known as “Scanning Force Microscopy (SFM)”. It is a microscope that can measure up to nanometer technology. In AFM, there is a pin, when this pin touches a bump and the pin will rise up. When the pin rise up, the laser that target to the pin and reflect to photodiode and let photodiode study, measure and decide the pin is rising or dropping. Its advantage is the performance of AFM is better than optical diffraction. To scan the object, we need to move either object or the pin. To move the object, we need some machine that can move in a small scale. The most challenging part is the machine need to move in small range. A small scale motion machine can cost the overall AFM in very high cost. To lower down the cost, we must find some material that is cheaper. After researching, we found that piezoelectric buzzer apply voltage, it will expend and push away the object. In this report, I had done many version of machine to make some motion. To make some motion, I need to apply some programming. I decide to use LabView as software and ELVIS II++ board as hardware. The reason of using LabView is because it has a very easy to study, it clear and graphical program. At the same time, ELVIS II++ is a test board by using LabView to control. From the programming part, ideally I will let X-axis from left move to right as a cycle and Y-axis will move up one coordinate. To prove this project works, I have to prove both axis can move.